Nootkatone inhibits the progression of glioblastoma by activating the ATF4-CHOP-CHAC1 pathway - Qian Wang; Xiumin Xue; Zhichao Chen; Wei Zhang; Yiming Qian; Danni Chen; Lin Lin; Yinfeng Yuan; Weiqiao Zhao; Zhihui Huang; Yongjie Wang (Molecular Medicine)
Abstract Glioblastoma multiforme (GBM) represents a primary brain tumor that is widely prevalent, and clinical drugs available for its treatment exhibit varying degrees of resistance. Nootkatone (NKT) is a functional sesquiterpene sourced from traditional Chinese medicine --Alpinia Oxyphylla Miq and has been reported to have a diverse range of pharmacological properties. However, it remains unknown whether there are effects of NKT on GBM. In this study, we found that NKT inhibited the growth of GBM cells in a dose-dependent manner in vitro. Subsequently, we observed that NKT suppressed the migration and arrested cell cycle at G2/M phase of GBM cells. Furthermore, NKT induced the death of GBM cells accompanied by an increase in reactive oxygen species (ROS) production. Mechanistically, we found that NKT inhibited the progression of GBM cells through activating the ATF4-CHOP-CHAC1 pathway in GBM cells. Furthermore, NKT-induced inhibition of migration and proliferation in GBM cells was partially restored by ATF4 or CHAC1 knockdown. Finally, we found that NKT inhibited the growth of tumor in GBM orthotopic mice model through activation of ATF4-CHOP-CHAC1 axis. Taken together, our findings show that NKT suppresses the growth and migration of GBM cells by activating the ATF4-CHOP-CHAC1 pathway, which in turn prevents the tumorigenesis of GBMs and provides a novel perspective for the development of drugs against GBM. Graphical Abstract